Medial forefoot fillet flap for primary closure of transmetatarsal amputation: A series of four cases. (December 2017) - Sidon, Eliezer; Shemesh, Shai; Rosenthal, Yoav; Heller, Snir; Velkes, Steven; Burg, Alon
Highlights: Transmetatarsal amputation is an effective treatment for various forefoot pathologies. A full-thickness skin cover for the wound is better tolerable in footwear. When a plantar flap is not feasible, the "spare-parts" technique can be used to cover the wound. The medial forefoot fillet flap technique allows full thickness skin cover to the wound without the need for other creative use of "spare parts". The two staged procedure enables easier wound and flap care. Abstract: Amputation of the forefoot is a salvage procedure for several forefoot acute or chronic infection. A good, sensate and durable skin cover is important for quicker and better rehabilitation. The use of filleted flaps (or "spare parts technique") has been published in the past as a creative technique. The purpose of this article is to introduce a reproducible, pre-planned, technique that requires less creativity for the use of the "spare parts". The authors describe a case series of 4 patients with deep infection and osteomyelitis of the forefoot, without involvement of the medial skin that underwent two staged procedure for transmetatarsal amputation with medial forefoot fillet flap. The first procedure was amputation of the 4 lesser metatarsal and the wound was left open. After a few days the second operation was done with amputation of the first metatarsal bone and using the filleted medial skin and subcutaneous tissue for closure of the wound. In conclusion the medial fillet flap is an effective method of covering large wounds after partial, lateral forefoot amputation. This method shortens the healing time of the patient, and in hospital stay. The authors recommend using the staged method when dealing with diabetic patients with partial, central and lateral forefoot deep infection and/or necrosis.